Direct electron transfer of laccase enzyme based on RGO/AuNPs/PNR - Mashayekhi, Fariba; Alijanianzadeh, Mahdi; Molaei Rad, Ahmad; Heydari, Payam (Archives of Advances in Biosciences, 2018)
Biofuel cell has been received much attention in recent years because the global energy demand increases every year. This paper presents a design of Mytheliophthora thermophile laccase on the electrode as a biocathode for biofuel cells based on direct electron transfer (DET) between the active site of the enzyme and reduced graphene oxide-gold nanoparticles-poly neutral red (RGO/AuNPs/PNR). The RGO/AuNPs/PNR/laccase biocathode was characterized by cyclic voltammetry (CV) method. The CV experiments demonstrated the activity, direct electron transfer, and stability of immobilized enzyme on the nanocomposite. The results showed the immobilized enzyme had good stability and performance on the nanocomposite after 10 days. Therefore, the presented method would be used in the design of biosensors or biocathode of biofuel cells.